Voltammetry with a carbon paste electroactive electrode used for the quality assessment of vegetable oils - Horská, Anna; Švancara, Ivan; Sýs, Milan (University of Pardubice, 2021)
This article introduces carbon paste electroactive electrodes in combination with voltammetric measurements as a useful tool for simple, low-cost, efficient, and semi-quantitative assessment of the quality of various vegetable oils. The respective method is based on anodic oxidation of electroactive organic compounds (namely: phenolic compounds and lipophilic vitamins) that naturally occur in the samples of interest and, in this case, being admixed in a small quantity directly into the carbon paste bulk. All the experiments were performed in 0.1 mol L−1 acetate buffer (pH 4.5) in the square-wave voltammetric mode. The results obtained have shown that the proposed procedure can be applied in food control to authenticate - as an electrochemical fingerprinting - the kind and the quality of a vegetable oil, including its freshness.
Keywords: carbon paste electroactive electrode; square-wave voltammetry; vegetable oils; lipophilic vitamins; phenolic compounds